2009
DOI: 10.1021/ie900310r
|View full text |Cite
|
Sign up to set email alerts
|

Energy Efficiency Limits for a Recuperative Bayonet Sulfuric Acid Decomposition Reactor for Sulfur Cycle Thermochemical Hydrogen Production

Abstract: A recuperative bayonet reactor design for the high-temperature sulfuric acid decomposition step in sulfur-based thermochemical hydrogen cycles was evaluated using pinch analysis in conjunction with statistical methods. The objective was to establish the minimum energy requirement. Taking hydrogen production via alkaline electrolysis with nuclear power as the benchmark, the acid decomposition step can consume no more than 450 kJ/mol SO 2 for sulfur cycles to be competitive. The lowest value of the minimum heati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…Now the catalyst technology used in PEMFC systems has been copied, and the electrodes are based on a catalyst supported by carbon-based materials deposited on gas diffusion layers. The sulphuric acid decomposition has been widely investigated in different studies, such as the one from Sandia National Laboratories [11], and most efforts have been devoted to the optimization of the SO 2 depolarized electrolysis (the electrochemical stage) to increase the global efficiency of the cycle [16]. Challenges for this process are the reduction of the overpotentials in the electrolysis step in order to improve the overall efficiency of the process-the development of high corrosion resistance materials due to the use of acid solutions.…”
Section: So2(aq) + 2h2o → H2so4(aq) + 2h + + 2e −mentioning
confidence: 99%
See 3 more Smart Citations
“…Now the catalyst technology used in PEMFC systems has been copied, and the electrodes are based on a catalyst supported by carbon-based materials deposited on gas diffusion layers. The sulphuric acid decomposition has been widely investigated in different studies, such as the one from Sandia National Laboratories [11], and most efforts have been devoted to the optimization of the SO 2 depolarized electrolysis (the electrochemical stage) to increase the global efficiency of the cycle [16]. Challenges for this process are the reduction of the overpotentials in the electrolysis step in order to improve the overall efficiency of the process-the development of high corrosion resistance materials due to the use of acid solutions.…”
Section: So2(aq) + 2h2o → H2so4(aq) + 2h + + 2e −mentioning
confidence: 99%
“…The results showed that the best catalyst was 60 wt % Pt-Cr/XC72R, which was better than the catalyst containing only platinum. In this work [11], the influence of the atomic ratio was also studied. The ratio 1:2 (Pt:Cr) resulted in equal or even better electrolysis performance than that of 60 wt % Pt/C.…”
Section: Combination Of Platinum With Other Metalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Kim et al proposed a thermodynamic design of a laboratory scale sulfuric acid decomposer for nuclear hydrogen production. Gorensek and Edwards combined a pinch analysis and statistical methods to calculate the minimum energy requirement of a bayonet‐type sulfuric acid decomposer, which consumed less than 450 kJ/(mol of SO 2 ) for sulfur cycles through alkaline electrolysis. Noguchi et al used a direct‐contact heat exchanger to recover heat and separate the undecomposed sulfuric acid in the sulfuric acid decomposition section with experimental results being in good agreement with an empirical correlation.…”
Section: Introductionmentioning
confidence: 99%